THE ROLE OF INFORMATION COMUNICATION TECHNOLOGY IN SIX SIGMA APPROACH IMPLEMENTATION - Kondić, Živko; Dušak, Vesna (Journal of Information and Organizational Sciences, 2006)
The article discusses Six Sigma Methodology as business philosophy assuring excellent product or service quality and continuous process improving to realise highest customer satisfaction level. There are analysed methodology advantages allowing defects and costs reduction and customer satisfaction improvement. Also, authors discuss methodology successful implementation according to gathering data on business processes regulation indicators values variation, and issued products or services performances. The results of implementation process of the Six Sigma Methodology in business system depend on prompt and correct data needed for statistical analysis, and its accessibility via organisation’ information system. Correlation between implementation of Six Sigma Methodology and information system development is so strong that non-conformances could cause the Six Sigma Methodology implementation fall.